There is more to control than the absence of autonomy: Conceptual distinctions between autonomy support, behavioral control, and psychological control - Tremblay, Maxime A (University of Ottawa (Canada), 2008)
The central purpose of the present thesis was to integrate the construct of autonomy support postulated by Cognitive Evaluation Theory and the literature on parental behavioral and psychological control. Its first specific objective was to demonstrate that autonomy support (AS), behavioral control (BC), and psychological control (PS) are distinct constructs. Its second specific objective was to ascertain unique associations between parental AS, BC, and PC, on one hand, and youth self-processes, internalizing symptoms, and externalized behaviors, on the other hand. Three studies were designed to achieve these goals. In Study 1A (N=342) and Study 1B (N=300), cross-sectional questionnaires were completed by undergraduate students and the dimensionality of parental behaviors was examined by means of confirmatory factor analyses. Results revealed that AS, BC, and PC are modelized in an optimal manner as distinct constructs. Study 2 ( N=138) consisted of a laboratory experiment designed to test the unique associations between AS, BC, and PC and youth self-processes, internalizing symptoms, and externalized behaviors. Study 3 (N=239) was a prospective field study that also endeavoured to examine the unique contribution of AS, BC, and PC to children functioning. In this study, self-processes, internalizing symptoms, and externalized behaviors were assessed over an 8-month competitive season. Globally, results from Study 2 and Study 3 revealed that AS predicted youth autonomous motivation, positive affect, satisfaction, and lower levels of internalizing symptoms. PC reached significant negative influences on youth functioning (i.e., controlled motivation, higher levels of impaired concentration, manifest anxiety and externalized behaviors). BC revealed positive associations with two beneficial outcome variables (i.e., autonomous motivation and lower levels of intended dropout), and a single negative consequence (i.e., manifest anxiety). Taken together, the findings of the three studies presented here provide support for the importance of distinguishing between AS, BC, and PC as basic functional dimensions that offer unique contribution to our understanding of the influence of socializing agents on youth development and functioning.
Keywords: Psychology, Behavioral.; Psychology, Developmental.